2018
DOI: 10.3390/molecules23113020
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Single Quadrupole Mass Spectrometer for Fingerprint Analysis: Venenum bufonis as a Case Study

Abstract: The mass spectrometry (MS) has been widely used for profiling chemical components of traditional Chinese medicine (TCM). However, there are few studies reporting quality control of TCM based on mass spectrometry fingerprint (MSF) due to its complicated operation and high cost. The aim of this study was to extend the application of MSF for quality evaluation of TCM. In this study, an MSF based on single quadrupole mass spectrometry method was established, and was successfully used for the quality control of Ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Among them, HPLC is the commonly used method for fingerprint analysis [15,16]. However, time-consuming, inability to withstand high pressure and large use of organic solvent are considered as its imperfections [17]. These problems have been successfully solved by UHPLC, which means introducing an environment-friendly approach to drug analysis achieved in a shorter run time with increasing resolution [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, HPLC is the commonly used method for fingerprint analysis [15,16]. However, time-consuming, inability to withstand high pressure and large use of organic solvent are considered as its imperfections [17]. These problems have been successfully solved by UHPLC, which means introducing an environment-friendly approach to drug analysis achieved in a shorter run time with increasing resolution [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, time-consuming, inability to withstand high pressure and large use of organic solvent are considered as its imperfections [17]. These problems have been successfully solved by UHPLC, which means introducing an environment-friendly approach to drug analysis achieved in a shorter run time with increasing resolution [17]. However, UHPLC fingerprints of traditional Chinese medicines often contain highly complex multivariate data that make their interpretation difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Taking advantage of selective ion monitoring (SIM) of single MS, multi‐component can be monitored in a targeted mode. Previous studies on TCM by single MS had demonstrated its superiority in quality control of TCM 12–14 …”
Section: Introductionmentioning
confidence: 99%